An IoT and Web-Based System for Efficient Waste Collection and Monitoring - Ellison Lim Jian Hung,; TS. DR. NAYEF ABDULWAHAB MOHAMMED ALDUAIS, (Applied Information Technology And Computer Science, 2024)
Traditional waste management systems are plagued by inefficiencies, high costs, and significant environmental impact. To tackle these challenges, this project proposes an IoT and web-based system for more effective waste collection and monitoring system. Utilizing Arduino IDE, C++, Python, ThingSpeak, Android Studio, PHP, MySQL, and cloud storage, the system integrates IoT sensors into waste bins for real-time data transmission and analysis, featuring modules for monitoring, reporting, visualization, notifications, user registration, staff management, and trash vehicle coordination. The parallel development methodology enabled smooth project progress and significant improvements in efficiency, coordination, and management. The system was tested with a test plan and User Acceptance Test (UAT), proving to be successfully developed and meeting user requirements. This comprehensive solution enables garbage organizations to use a variety of tools in the system to optimize waste collection. By deploying this comprehensive solution, businesses is able operate at full scale, contributing to smarter and more sustainable urban settings.